Growth and CD4 patterns of adolescents living with perinatally acquired HIV worldwide, a CIPHER cohort collaboration analysis. Issue 3 (7th March 2022) - ,; Jesson, Julie; Crichton, Siobhan; Quartagno, Matteo; Yotebieng, Marcel; Abrams, Elaine J.; Chokephaibulkit, Kulkanya; Le Coeur, Sophie; Aké‐Assi, Marie‐Hélène; Patel, Kunjal; Pinto, Jorge; Paul, Mary; et al.
Abstract: Introduction: Adolescents living with HIV are subject to multiple co‐morbidities, including growth retardation and immunodeficiency. We describe growth and CD4 evolution during adolescence using data from the Collaborative Initiative for Paediatric HIV Education and Research (CIPHER) global project. Methods: Data were collected between 1994 and 2015 from 11 CIPHER networks worldwide. Adolescents with perinatally acquired HIV infection (APH) who initiated antiretroviral therapy (ART) before age 10 years, with at least one height or CD4 count measurement while aged 10–17 years, were included. Growth was measured using height‐for‐age Z‐scores (HAZ, stunting if <‐2 SD, WHO growth charts). Linear mixed‐effects models were used to study the evolution of each outcome between ages 10 and 17. For growth, sex‐specific models with fractional polynomials were used to model non‐linear relationships for age at ART initiation, HAZ at age 10 and time, defined as current age from 10 to 17 years of age. Results: A total of 20, 939 and 19, 557 APH were included for the growth and CD4 analyses, respectively. Half were females, two‐thirds lived in East and Southern Africa, and median age at ART initiation ranged from <3 years in North America and Europe to >7 years in sub‐Saharan African regions. At age 10, stunting ranged from 6% in North America and Europe to 39% in the Asia‐Pacific; 19% overall had CD4 counts <500 cells/mm 3 . Across adolescence, higher HAZ was observed in females and among those in high‐income countries. APH with stunting at age 10 and those with late ART initiation (after age 5) had the largest HAZ gains during adolescence, but these gains were insufficient to catch‐up with non‐stunted, early ART‐treated adolescents. From age 10 to 16 years, mean CD4 counts declined from 768 to 607 cells/mm 3 . This decline was observed across all regions, in males and females. Conclusions: Growth patterns during adolescence differed substantially by sex and region, while CD4 patterns were similar, with an observed CD4 decline that needs further investigation. Early diagnosis and timely initiation of treatment in early childhood to prevent growth retardation and immunodeficiency are critical to improving APH growth and CD4 outcomes by the time they reach adulthood.